Long‐term effect of extracorporeal magnetic innervation for post‐prostatectomy urinary incontinence: 1‐year follow‐up. Issue 1 (8th October 2021) - Terzoni, Stefano; Ferrara, Paolo; Mora, Cristina; Destrebecq, Anne
Abstract: Urinary incontinence after radical prostatectomy is a common and bothersome problem. Pelvic floor muscle training (PFMT) is supported by strong recommendations in the European guidelines as the first‐choice rehabilitation method. Extracorporeal magnetic innervation (ExMI) has been studied in a previous pilot investigation by our team and seemed useful for shortening the duration of the rehabilitation programme, although patients still need to perform maintenance PFMT regardless of the method chosen for rehabilitation. Very few data exist in literature about its long‐term effects on men; the need for additional evidence therefore remains. To investigate the long‐term effects of ExMI associated with maintenance PFMT, compared to PFMT alone, in maintaining continence after the end of a rehabilitation programme. Follow‐up study on 83 rehabilitated patients (67 PFMT, 16 ExMI). All patients were instructed by a nurse specialist to perform the same maintenance PFMT exercises, based on the literature. Pad‐test was performed by all patients after 3, 6 and 12 months from the end of the rehabilitation programme. As in previously published studies, rehabilitation was defined as leakages <10 g/day based on a literature definition. A mixed effects linear model was used to assess differences between residual leakages over time. Both PFMT and ExMI gave clinically satisfactory results during the whole follow‐up period, without statistically significant differences in the leakages. However, the correlation coefficients suggest that the results are more stable in the PFMT group over time, with less variations in the residual leakages. ExMI can be used during rehabilitation to speed up recovery, but PFMT are still needed for maintenance and provide better results in the long run, even though ExMI also provides satisfactory continence outcomes at follow‐up. Studies on larger samples are needed to confirm these findings.